Effect of plastic and seaweed shelters on the skin microbiome of lumpfish Cyclopterus lumpus used as cleaner fish in aquaculture pens - Ása Jacobsen; Agnes Mols Mortensen; Kirstin Eliasen; Elin Egholm; Marner Nolsøe; Ása Johannesen (PLoS ONE, 2025)
Atlantic salmon ( Salmo salar ) aquaculture is a major industry in several countries worldwide and a growing enterprise in others. One of the main challenges the industry faces is infestations with the parasitic copepod Lepeoptheirus salmonis , or salmon lice. Several different chemical and mechanical methods are available for alleviating the problem, but often at cost to salmon welfare and/or the environment. In some regions cleaner fish have been introduced to farming facilities as an environmentally and salmon welfare friendly option for reducing sea lice infestations. In some North Atlantic countries, lumpfish ( Cyclopterus lumpus ) are being used as cleaner fish. However, poor welfare and high mortality rates of lumpfish in salmon farming are frequent issues, and the need to improve lumpfish welfare is great. One adaptation for salmon farms is to provide the lumpfish with shelters to meet their need to rest and hide. Plastic shelters are the most widely used form, but seaweed shelters have more recently also been applied as a more natural solution. This project investigated the potential effect of seaweed and plastic shelters on the skin and gill microbiome of lumpfish and any potential correlation to their welfare. In an experimental setup in a commercial salmon farming facility, lumpfish from pens with either plastic or seaweed shelters were sampled over a period of approximately three months. The results showed that the bacterial communities on the two shelter types were significantly different and fewer potentially pathogenic bacteria dominated the skin microbiome of lumpfish living with seaweed shelters than of those living with plastic shelters. No differences were detected in the welfare of the lumpfish and further investigations are needed to clarify any potential implications of the differences detected in the skin microbiome of lumpfish including responses to stressful conditions.